Proof technology and computation - Schwichtenberg, Helmut; Spies, Katharina (IOS Press, 2006)
Proof technology will become an established field in software engineering. It generally aims at integrating proof processing into industrial design and verifications tools. The origins of this technology lie in the systematic understanding of a fully-fledged, precise notion of proof by mathematics and logics. Using this profound understanding, computer scientists are able to implement proofs, to check and create them automatically and to connect the concepts of proof and programs in a deep way. Via this, connection proofs are used to support the development of reliable software systems. Software engineers have integrated proof processing into industrial development tools, and these implementations are now getting very efficient. The chapters deal with: The benefits and technical challenges of sharing formal mathematics among interactive theorem provers; proof normalization for various axiomatic theories; abstraction-refinement framework of temporal logic model checking; formal verification in industrial hardware design; readable machine-checked proofs and semantics and more.